Haematological Studies in Wild Ungulates of Thar Desert - Gehlot, H. S.; Vyas, Vittlesh (Indian Forester, 2021)
The present study comprised a different aged group of wild ungulates (14 Chinkara, 19 Bluebull and 12 Blackbuck) were conducted to evaluate the hematological parameters for assessing the health status in Thar Desert. The combined value of both seÃ— es of chinkara revealed Red Blood Cell (RBC) with a total count of 9.67 Â± 3.02Â Ã— 1012 per cu. mm, The Hemoglobin (Hb) concentration of 13.87 Â± 3.35 gm/dl, Mean Corpuscular Volume (MCV) of 37.71 Â± 13.30 fL. Mean Corpuscular Hemoglobin (MCH) of 15.05 Â± 6.08, Total White Blood Corpuscles (WBC) was 20.66 Â± 43.14 Ã— 109 per cu. mm. and the combined value of both sexes of Blackbuck revealed RBC with a total count of 12.44 Â± 1.27 Ã— 1012 per cu. mm, The Hb concentration of 14.39 Â± 2.59 gm/dl, MCV of 31.38 Â± 3.62fL, MCH of 11.58 Â± 1.73,Total WBC was 12.57 Â± 8.69 Ã— 10103 per cu. mm. While the Combined Value of Both Sexes of Bluebull revealed RBC with a total count of 9.58 Â± 1.81 Ã— 101012 per cu. mm, The Hb concentration of 12.57 Â± 2.43 gm/dl, MCV of 36.57 Â± 10.34, MCH of 13.54 Â±Â 3.54, Total WBC was 38.65 Â± 80.8 Ã— 109/L